The Effect of Sodium Nitroprusside Treatment on Storage Ability of Fresh-Cut Potato - Yukexin Dai; Hong Xie; Xiaoyan Zhao; Yanyan Zheng (Foods, 2023)
Quality deterioration is a major problem restricting the fresh-cut potato industry. The present study investigated the effect of sodium nitroprusside (SNP) treatment on the quality of fresh-cut potatoes during short-term storage. The treatment was carried out immediately either before or after cutting, using an SNP concentration of 200 μmol/L. The results showed that SNP treatment inhibited the accumulation of malondialdehyde (MDA) and total soluble solids (TSSs). SNP treatment also decreased the firmness, chewing properties, and ascorbic acid (AsA) content in potatoes, maintaining high levels of total phenols (TPs), total flavonoids (TFs), nitric oxide (NO), and superoxide dismutase (SOD). Furthermore, SNP treatment restrained the rise of phenylalanine ammonia-lyase (PAL), peroxidase (POD), and polyphenol oxidase (PPO), as well as the electrolyte leakage (EL) rate. After SNP treatment, the nitrite content in the potatoes was within security scope. Comparing potatoes treated before and after cutting, the best result was noted in the potatoes soaked in SNP before cutting, which displayed the smallest losses in firmness (11.24%), chewing properties (34.30%), and AsA (40.35%), and maximum increases in TPs (32.84%), TFs (2.83−time), NO (76.11%), and SOD activity (93.15%). Moreover, this group presented the minimum MDA content, EL rate, and TSS values and the lowest PAL, POD, and PPO activities. These results indicated that 200 μmol/L SNP applied for 20 min, particularly before cutting, is an efficient alternative technology that can be used in the fresh-cut potato industry.